Completing the Monetary Union of Europe as Mid-term Solution of the Euro Crisis - Justina A.V. Fischer; Francesco Pastore (Institute for the Study of Labor (IZA), 2015)
This research note discusses the Euro crisis in Greece in light of the referendum of July the 5th. It lays out the social and political costs of a GREXIT, but also of a continuing austerity policy. It proposes a reform policy fostering growth in Greece and discusses the role of conditionality. Finally, the important role of mid-left parties is highlighted.
Keywords: E12; E62; F15; F16; F33; F55; H12; H50; H63; O42; O43; 330; IMF; Germany; Greece; Euro; Europe; Monetary Union